Penyuluhan Anti Bullying Sebagai Upaya Pencegahan Tindakan Bullying Pada Siswa SD Negeri Babakan - Vidhia Sinthianingputri; Nur Dina Khasanah; Selvia Dewi Sagita; Muhammad Hafid Nurfadilah; Miftakhul Awaliyah; Dian Rif’iyati (Universitas Maritim AMNI Semarang, 2023)
Bullying behavior from time to time continues to be a thing that haunts Indonesian children, especially in the Elementary School (SD) environment. This activity aims to provide information about bullying and prevention efforts, so as to avoid bullying and prevent bullying from happening again. The method used in this activity is in the form of counseling using PowerPoint media and videos as learning aids. The results show that there is still a lack of knowledge of students about bullying including the forms and types of bullying and their impacts and in fact these actions are often carried out without realizing it. Through this counseling method students can easily understand bullying so they can avoid doing it and prevent bullying from happening again.